2018
DOI: 10.1002/cncr.31764
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent overweight and obesity and the risk for pancreatic cancer among men and women: a nationwide study of 1.79 million Israeli adolescents

Abstract: BACKGROUND: There is growing concern regarding the impact of adolescent obesity on adult health. The objective of this study was to evaluate the association between body mass index (BMI) in late adolescence and the incidence of pancreatic cancer during adulthood. METHODS: The authors analyzed a cohort of 1087,358 Israeli Jewish men and 707,212 Jewish women who underwent a compulsory physical examination between ages 16 and 19 years from 1967 to 2002. Pancreatic cancer incidence through December 31, 2012 was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The article written by Levi et al reported that adolescent obesity was associated with an increased risk of subsequent pancreatic cancer (hazard ratio, 4.06; 95% confidence interval, 2.80‐5.88) . This finding was partially compatible with the study by Li et al that demonstrated that pancreatic cancer was associated with the onset of obesity in early adulthood (odds ratio, 2.58; 95% confidence interval, 1.70‐3.90) .…”
supporting
confidence: 54%
See 2 more Smart Citations
“…The article written by Levi et al reported that adolescent obesity was associated with an increased risk of subsequent pancreatic cancer (hazard ratio, 4.06; 95% confidence interval, 2.80‐5.88) . This finding was partially compatible with the study by Li et al that demonstrated that pancreatic cancer was associated with the onset of obesity in early adulthood (odds ratio, 2.58; 95% confidence interval, 1.70‐3.90) .…”
supporting
confidence: 54%
“…A cohort design with a long‐term follow‐up is needed to detect the development of pancreatic cancer. The study by Levi et al has such a strength, with a median follow‐up of 23 years. Second, diabetes mellitus has been found to be associated with an increased risk of subsequent pancreatic cancer .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The authors demonstrate a positive association between body mass index (BMI) in and above the 75th percentile with such risk, from the 75th percentile and above for men and from the 95th percentile for women. Great strides are apparent in many fields and disciplines, which are enabled by trends and developments in society, science, economy, and the multifaceted interfaces between them.…”
mentioning
confidence: 99%
“…1 The authors demonstrate a positive association between body mass index (BMI) in and above the 75th percentile with such risk, from the 75th percentile and above for men and from the 95th percentile for women. 1 The authors demonstrate a positive association between body mass index (BMI) in and above the 75th percentile with such risk, from the 75th percentile and above for men and from the 95th percentile for women.…”
mentioning
confidence: 99%